BUILDING A DIGITAL-BASED (POST-PANDEMIC) MODERATE MUSLIM URBAN COMMUNITY: REFLECTION ON THE INTERPRETATION OF DA’WAH VERSES - Jauhar Azizy; Sihabussalam Sihabussalam; Desmaliza Desmaliza (Akademika : Jurnal Pemikiran Islam, 2022)
Extremism is a common problem that needs to be resolved by various parties. One of the causes of extremism is the paradigm of primordialism and ethnocentrism. This paradigm holds that individuals or groups themselves are the best and tend to demean other groups. Socio-religious changes due to the Covid-19 pandemic have exacerbated the situation of a pluralistic Indonesian society. This has even permeated through the cyberspace. This article reflects on the interpretation of the verses calling for a response to the post-Covid-19 condition of Muslim urban communities. This article aims at maintaining the harmony of Indonesian society, especially urban Muslims, while at the same time reinforcing a moderate attitude after the outbreak. This study uses a qualitative research method with a content analysis approach. This article concludes that the reflection of these da'wah verses leads to the importance of digital da'wah as a means of building (post-pandemic) moderate urban Muslim communities by upholding the goals of Islam, namely rahmatan li al-‘alamin, and collective benefit. There are six ways to build a moderate, digital-based Muslim urban community: First, through media literacy and digital literacy; second, a preacher must have the courage to expose his potential; third, grounding the content of moderation on social media; fourth, forming a group of moderate-minded digital media account managers; fifth, strengthening collaboration with influencers (people who are influential in social media); sixth, courteous communication.